Fatty acid composition, antioxidant levels and oxidation products development in the muscle tissue of Merluccius merluccius and Dicentrarchus labrax during ice storage. (November 2016) - Celano, Rita; Campone, Luca; Piccinelli, Anna Lisa; Acernese, Fausto; Nabavi, Seyed Mohammad; Di Bella, Giuseppa; Rastrelli, Luca
Abstract: Muscle tissue of two Mediterranean fish species ( Merluccius merluccius, and Dicentrarchus labrax ) were kept on ice for 7 days and at 0, 1, 2, 4, 5, 6, 7 day storage points, the levels of hydrophilic, lipophilic and enzymatic antioxidants, the fatty acids composition as well as the oxidative damage to polyunsaturated fatty acids (PUFA), proteins and DNA were measured. As shown by regression analyses, ubichinones (CoQn ), α-tocophetol (Vit E), glutathione peroxidase (GPx) activity, reduced glutathione (GSH), triglyceride (TG), phospholipid (PL) and PL-PUFA showed significant decreasing in function of storage time whereas free fatty acids (FFA), TBARS and Protein carbonyl, that negatively affect fish quality, are strongly linearly inversely correlated with Gpx, Vit E and GSH. Vitamin C and CoQn H2 levels decreased by 47.6–50.0% and 64.9–64.3% on the first day of storage on ice in Dicentrarchus labrax and Merluccius merluccius respectively and disappeared entirely after 4-day storage. Their decline occurred at a faster rate than that of Vit E and CoQn which in turn was faster than decline of GSH and SOD and GPx activities. Lipophilic antioxidant and Vit C levels represent a reliable marker of oxidative stress during storage. Highlights: Endogenous antioxidants decreased during ice storage in fish. Lipid oxidation in fish is linked to decline of CoQH2, vitamin E and vitamin C. Their determination might be valuable for the assessment of fish freshness and quality. High levels of n −3 fatty acids were found in the fish species studied.